2017
DOI: 10.3389/fpsyg.2017.00358
|View full text |Cite
|
Sign up to set email alerts
|

Does Hunger Contribute to Socioeconomic Gradients in Behavior?

Abstract: Recent research has uncovered many examples of socioeconomic gradients in behavior and psychological states. As yet there is no theoretical consensus on the nature of the causal processes that produce these gradients. Here, I present the hunger hypothesis, namely the claim that part of the reason that people of lower socioeconomic position behave and feel as they do is that they are relatively often hungry. The hunger hypothesis applies in particular to impulsivity-hyperactivity, irritability-aggression, anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 106 publications
2
18
0
Order By: Relevance
“…We recommend that further investigation is needed into the differences in response seen in these two types of tasks. It has also previously been hypothesised that individuals of lower socioeconomic status may simply be hungrier than other individuals, which may underlie differences seen in impulsivity (Nettle, 2017). We tested for this across all three of our studies finding no evidence of an association between current hunger and childhood socioeconomic statues when controlling for the amount of time since people had last eaten.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We recommend that further investigation is needed into the differences in response seen in these two types of tasks. It has also previously been hypothesised that individuals of lower socioeconomic status may simply be hungrier than other individuals, which may underlie differences seen in impulsivity (Nettle, 2017). We tested for this across all three of our studies finding no evidence of an association between current hunger and childhood socioeconomic statues when controlling for the amount of time since people had last eaten.…”
Section: Discussionmentioning
confidence: 83%
“…As it has previously been suggested that hunger and measures of socioeconomic status may be associated (Nettle 2017) we initially ran a model to see if hunger was predicted by childhood IMD, whilst controlling for time since participants had last eaten, finding that time since a person had eaten did predict hunger but childhood IMD did not (Appendix, Table 5, Model 1).…”
Section: Models Predicting Impulsivitymentioning
confidence: 99%
See 1 more Smart Citation
“…"Within affluent societies the poor experience a substantial burden of hunger, despite obtaining sufficient or excess calories on average" (Nettle, 2017) . Considered by itself, abundant food produced by other people may only modestly convince the mood system of food security.…”
Section: The Puzzle Of So Much Foodmentioning
confidence: 99%
“…Current support for the existence of such a direct effect is weak (Häusser et al, 2019). However, even in the absence of such a direct effect, there are pathways by which hunger could cause cooperation to break down in real-world settings, pathways which stem from the fact that emotional responses to the behaviour of others have often been found to be different in hungry people (Nettle, 2017). For example, hungry people might have the same initial prosocial motivations as non-hungry people, but respond more negatively or less forgivingly to the behaviour of others, leading to a downwards spiral of cooperation.…”
Section: General Introductionmentioning
confidence: 99%